Robotically Assisted Single Anastomosis Duodenoileal Bypass after Previous Sleeve Gastrectomy Implementing High Valuable Technology for Complex Procedures. (30th September 2015) - Vilallonga, Ramon; Fort, José Manuel; Caubet, Enric; Gonzalez, Oscar; Balibrea, José Maria; Ciudin, Andrea; Armengol, Manel
Abstract : Staged bariatric procedures in high risk patients are a common used strategy for morbid obese patients nowadays. After previous sleeve gastrectomy, surgical treatments in order to complete weight loss or comorbidities improvements or resolutions are possible. One strategy is to perform a novel technique named SADI (single anastomosis duodenoileal bypass-sleeve). We present the technique for totally intracorporeal robotically assisted SADI using five ports and a liver retractor. We aim to see if the robotic technology offers more advantageous anastomosis and dissection obtained by the robotic approach in comparison to standard laparoscopy. The safety, feasibility, and reproducibility of a minimally invasive robotic surgical approach to complex abdominal operations such as SADI are discussed.